Decision to return to sport participation after anterior cruciate ligament reconstruction, Part II: Self-reported and functional performance outcomes - Werner, J. L.; Burland, J. P.; Mattacola, C. G.; Toonstra, J.; English, R. A.; Howard, J. S. (Journal of Athletic Training, 2018)
Context: Anterior cruciate ligament (ACL) reconstruction (ACLR) is the most commonly used method for helping athletes regain function and return to preinjury activity levels after ACL injury. Outcomes after ACLR have suggested that athletes return to a level of function that would support a return to sport participation; however, in a recent meta-analysis, pooled return rates were only 55%. It is unclear whether this discrepancy is a result of functional impairments.